A "Smart" Hollandite DeNOx Catalyst: Self‐Protection against Alkali Poisoning1. Issue 2 (22nd November 2012) - Huang, Zhiwei; Gu, Xiao; Wen, Wen; Hu, Pingping; Makkee, Michiel; Lin, He; Kapteijn, Freek; Tang, Xingfu
<x xml:space="preserve">Abstract</x> Banish the villains to their own realm: Biomass has gained widespread attention as a renewable energy source. However, commercial catalysts used in power plants (co‐)fuelled by biomass are deactivated by the alkali‐rich flue gas (see graph, black line). In contrast, one of two types of active sites in a promising alkali‐resistant hollandite catalyst traps alkali‐metal ions to free up the catalytically active sites for the reduction of NO by NH3.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>